Dominant expression of type III hyperlipoproteinemia. Pathophysiological insights derived from the structural and kinetic characteristics of ApoE-1 (Lys146-->Glu). - Mann, W A (1995)
Type III hyperlipoproteinemia is characterized by delayed chylomicron and VLDL remnant catabolism and is associated with homozygosity for the apoE-2 allele. We have identified a kindred in which heterozygosity for an apoE mutant, apoE-1 (Lys146-->Glu), is dominantly associated with the expression of type III hyperlipoproteinemia. DNA sequence analysis of the mutant apoE gene revealed a single-point mutation that resulted in the substitution of glutamic acid (GAG) for lysine (AAG) at residue 146 in the proposed receptor-binding domain of apoE. The pathophysiological effect of this mutation was investigated in vivo by kinetic studies in the patient and six normal subjects, and in vitro by binding studies of apoE-1 (Lys146-->Glu) to LDL receptors on human fibroblasts and to heparin. The kinetic studies revealed that apoE-1 (Lys146-->Glu) was catabolized significantly slower than apoE-3 in normals (P < 0.005). In the proband, the plasma residence times of both apoEs were substantially longer and the production rate of total apoE was about two times higher than in the control subjects. ApoE-1 (Lys146-->Glu) was defective in interacting with LDL receptors, and its ability to displace LDL in an in vitro assay was reduced to 7.7% compared with apoE-3. The affinity of apoE-1 (Lys146-->Glu) to heparin was also markedly reduced compared with both apoE-2 (Arg158-->Cys) and apoE-3. These abnormal in vitro binding characteristics and the altered in vivo metabolism of apoE-1 (Lys146-->Glu) are proposed to result in the functional dominance of this mutation in the affected kindred.